Risk Factors Associated with Urinary Tract Infection in Children - Gupta, Murli Manohar; Shrestha, Suman Ram (Journal of Nepalgunj Medical College, 2021)
Introduction: Urinary tract infection is infection leading to an inflammatory response in the epithelium of the urinary tract. Urinary tract infection is defined as the growth of significant number of organisms of a single species in the urine, in the presence of symptoms. Significant bacteriuria is a growth with colony count of >105 / ml of a single species in a mid-stream clean catch urine sample. Aims: To find the prevalence of urinary tract infection in children with fever and its risk factor. Methods: A hospital based cross sectional observational study was performed in Nepalgunj Medical College, Kohalpur from October 2019 to October 2020.Children of age two months to 14 years admitted in Department of Pediatrics and visiting in outdoor fulfilling inclusion criteria were taken for the study. Detailed history and examination was performed. Data related to age, sex, predisposing risk factors of Urinary tract infection, symptoms and relevant investigations was carried out in all patients. Results: Among 135 children, maximum 62(45.92%) children were in the age group 1-5 years. There were 70(51.85) male and 65(48.14) female children. The prevalence of culture positive of urinary tract infection was 19.20%. Pyuria was more significant in females in comparison to male, more common in age group less than 5 years. 26 children were culture positive among which males to female ratio in urine culture positive cases were 1: 2.3 and majority had E.coli positive in urine culture sample. Apart from the female children urinary tract infection was commonly seen in uncircumcised male comprising of 8(11.42%) of total male children. Conclusion: In children presenting with fever, urinary tract infection was one of the common causes. It was most common in children less than 5 years, female gender and uncircumcised male children were two commonly associated risk factors